Rough diamonds - Park, Seung-ho
Discover the four traits of the best performing, but least known, breakout firms in BRIC countries "Rough diamonds" are the best performing firms in the BRIC (Brazil-Russia-India-China) countries. These firms compare favorably with the top 500 firms and the top 25 manufacturing firms in their countries and comparable firms worldwide, exceeding them profit margins and return on assets over an extended time period. This book outlines who these firms are and explains their exemplary performance through the Four Cs for Sustaining High Performance: Capitalizing on late development; Creating Market Inclusive Niches; Crafting Operational Excellence; and Cultivating Profitable Growth